2013
DOI: 10.1103/physrevb.87.235135
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent and anisotropic optical response of layered Pr0.5Ca1.5MnO4

Abstract: Temperature-dependent and anisotropic optical response of layered Pr0.5Ca1.5MnO4 probed by spectroscopic ellipsometry Majidi, M. A.; Thoeng, E.; Gogoi, P. K.; Wendt, F.; Wang, S. H.; Santoso, I.; Asmara, T. C.; Handayani, I. P.; van Loosdrecht, P. H. M.; Nugroho, A. A.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
(33 reference statements)
3
14
1
Order By: Relevance
“…This finding is in agreement with a previous study of Mn-O bonds in La 1−x Sr 1+x MnO 4 , which suggested that the structure is very sensitive to the occupation of e g orbitals [32,33]. We also note that a recent optical conductivity study of Pr 0.5 Ca 1.5 MnO 4 suggests that the oxygen p-orbital orientation changes in each temperature regime [29]. A change in oxygen p-orbital orientation will influence the manganese e g -orbital orientation because the oxygen ions are displaced along the directions of the Mn-O-Mn bonds.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with a previous study of Mn-O bonds in La 1−x Sr 1+x MnO 4 , which suggested that the structure is very sensitive to the occupation of e g orbitals [32,33]. We also note that a recent optical conductivity study of Pr 0.5 Ca 1.5 MnO 4 suggests that the oxygen p-orbital orientation changes in each temperature regime [29]. A change in oxygen p-orbital orientation will influence the manganese e g -orbital orientation because the oxygen ions are displaced along the directions of the Mn-O-Mn bonds.…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis of the rotation mode intensity suggests that fluctuations of this mode accompanying the CO-OO transition are small enough to justify a mean field model. This finding is in agreement with previous studies on PCMO, where the CO below the transition could be approximately described by a mean field model [29]. Based on this observation, we propose that one of the physical phenomena behind the charge and orbital order in Pr 0.5 Ca 1.5 MnO 4 is the change in Mn-O bond lengths.…”
Section: Discussionsupporting
confidence: 93%
“…The penetration depth of the pump and the probe was approximately matched by using a small 0.5°grazing incident angle of the x-ray beam. The estimated pump and probe depths are approximately 40 and 50 nm [32], respectively. The footprint of the x-ray probe beam on the sample surface was minimized by reducing the vertical beam size to 10 μm [33].…”
Section: Methodsmentioning
confidence: 93%
“…The parameter I reflects the electrons excited by photons during the selected energy range. It can be defined as39:…”
Section: Resultsmentioning
confidence: 99%